2013
DOI: 10.1007/s00296-012-2616-9
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatic manifestations of euthyroid, anti-thyroid antibody-positive patients

Abstract: The aim of this study is to define the rheumatic manifestations of euthyroid patients with chronic lymphocytic thyroiditis (CLT) but without a well-defined connective tissue disease. Forty-six consecutive patients with anti-thyroid peroxidase (αTPO) and/or anti-thyroglobulin antibodies (αTG), and normal thyroid function in the absence of a well-defined connective tissue disease were included in a case-cohort study. Arthralgias were a presenting complaint in 98 % of patients. Fibromyalgia syndrome was found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 34 publications
1
20
0
2
Order By: Relevance
“…2 Arthralgia and even arthritis of small joints such as the wrist and hand are found in patients with thyroid autoimmunity without concomitant connective tissue disease. 7,35 Punzi et al 47 observed antimicrosomal antibodies in the synovial fluid of patients one year prior to antibody detection in serum, and one year prior to the diagnosis of hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Arthralgia and even arthritis of small joints such as the wrist and hand are found in patients with thyroid autoimmunity without concomitant connective tissue disease. 7,35 Punzi et al 47 observed antimicrosomal antibodies in the synovial fluid of patients one year prior to antibody detection in serum, and one year prior to the diagnosis of hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…3 Nearly all Hashimoto thyroiditis patients have high serum concentrations of antibodies against one or more thyroid antigens that are produced by lymphocytic infiltrate in the thyroid gland or, to a small extent, by regional lymph nodes or bone marrow. 4 Hypothyroidism and rheumatic diseases share common clinical findings such as arthralgias, arthritis, myalgias, myopathy and fatigue, [6][7][8] which need to be correctly diagnosed to be properly treated. Knowing the degree of association between rheumatic and thyroid diseases may help the clinician to make the correct decision.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, ATD has been linked independently with fibromyalgia and chronic widespread pain (CWP) [16,17]. This expands the argument that autoimmune thyroiditis itself may exert immunological sequelae beyond the confines of the thyroid gland [15].…”
Section: Introductionmentioning
confidence: 95%
“…Tagoe и соавт. [19] у 98% пациентов с антителами к гормонам ЩЖ и нормальным уровнем ТТГ встречались полиартралгии, а у 26% -синовит суставов кистей и/или лучезапястных суставов. При этом достовер-ные диагнозы каких-либо определенных РЗ были отверг-нуты ревматологами у всех больных.…”
Section: особенности клинической картины ревматоидного артрита на фонunclassified
“…Однако нередко в крови больных АЗЩЖ обнаруживаются и дру-гие антитела, в том числе РФ, антинуклеарный фактор, антитела к Ro [18][19][20]. При ДТЗ аутоантитела способны стимулировать тиреоциты, что приводит к развитию ги-пертиреоза.…”
unclassified